Synthesis of functional materials for carbon capture via microfluidic platform - Yew, Maxine (2021)
Carbon capture and storage has been a trending topic ever since the call to control and curb CO2 emission was made global. Attempts and researches to improve the efficiency of existing capture technologies have flourished, with recent studies on carbon removal with reactive solvents venturing into the discipline of microfluidics to benefit from the small and precise.